Outcomes of Urethral Strictures Managed with Endoscopic Urethrotomy versus Urethroplasty: A Retrospective Comparative Analysis of 80 Cases - Naseeb Dad, Sajid Malik, Wasim Sarwar Bhatti, Masoom Ali Shah, Zeeshan Qadeer, Bilal Suria, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the clinical outcomes of urethral strictures treated with endoscopic urethrotomy and urethroplasty in terms of urinary flow rates, recurrence, and overall success. Study Design: Retrospective comparative study Methods: Eighty male patients with urethral strictures were retrospectively analyzed. After obtaining informed consent, demographic and clinical characteristics (age, BMI, and comorbidities) were documented. Patients were allocated into two groups: Group I (n=40) underwent urethroplasty, while Group II (n=40) received endoscopic urethrotomy. Follow-up ranged between 4–6 months, with treatment success, recurrence, and maximum urinary flow rate (Qmax) as primary outcomes. Statistical analysis was performed using SPSS v22. Results: The mean age of patients was 51.2 ± 12.8 years in Group I and 52.1 ± 11.3 years in Group II, with mean BMI of 24.9 ± 3.1 and 25.5 ± 2.8 kg/m², respectively. Dysuria, urinary retention, and frequency were the predominant presenting complaints. Infection was the most frequent etiology (61.2%), followed by trauma (22.5%) and iatrogenic causes (16.3%). The membranous urethra was the most common site of involvement. Postoperatively, mean Qmax improved significantly in the urethroplasty group (16.4 ± 5.2 mL/s) compared to the urethrotomy group (9.6 ± 4.7 mL/s, p=0.03). Treatment success was achieved in 85% of urethroplasty cases compared with 52.5% in the urethrotomy group. Recurrence was observed in 10% of urethroplasty patients versus 27.5% of urethrotomy patients. Conclusion: Urethroplasty demonstrated superior functional outcomes and a lower recurrence rate compared with endoscopic urethrotomy. The findings reinforce urethroplasty as the preferred treatment for definitive management of urethral strictures. Keywords: Urethral stricture, Urethroplasty, Urethrotomy, Qmax, Recurrence